Occupational eye traumatism of members of vessel`s crews of the Northern Water`s Basin - Shapovalov KA; Shapovalova PK (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2019)
Introduction: Occupational eye traumatism of members of vessel`s crews of the Northern Water`s Basin are relevant, but little studied medical problem. Material and methods: The analysis of a continuous sample of various eye traumatism in 79 patients, working on the vessels of the basin was carried out. Analytical and statistical methods were used for the analysis. Results: In water transport, eye traumatism was found in men from among of members of vessel`s crews significantly more often than in women (P <0.001). Every second injury occurs to sailors aged 20-29. In 30-39 and 40-49 years - their number is reduced by half. Individual cases of eye damage were observed in persons under 20 years and over 50 years. In every second case of an injury to the eye, of members of the technical operation service ("machine command") received; operation - 47.3%; production - 2.7%. Among the injured there were no representatives of the radio-technical service, product processing, household, medical and sanitary. Outcomes of eye injuries of members of vessel`s crews of the Northern Water`s Basin during the study period should be considered good. Most sailors return to work in their specialty. Disability group III is set in 2.7% of cases. Conclusions: 1. The socio-economic significance of the industrial eye traumatism of the transport and fishing fleets of the Northern Water`s Basin allows to classify members of vessel`s crews as a group at increased risk of this occurrence of injuries. 2. In the general structure of this type of occupational traumatism, members of vessel`s crews of ocular organ damage constitute 3.6% of cases and occupy the sixth rank position. 3. During the voyages on ships, workers' eyes were injured by 40.2% of observations and foreign bodies (34.6%; P<0.05). Contusions (18.2%; P<0.05) and burns (7.0%; P<0.01) are significantly inferior to them. 4. Ordinary composition: motorists and sailors are most vulnerable to eye injuries (P<0.05). Mechanics, navigators and other ship specialists made up only one fourth of the victims. 5. Most of the eye damage on ships occurs during the maintenance and repair of machinery in the engine room; maintenance of deck machinery (P<0.01); repair of electrical equipment (P<0.001); general ship works associated with ramps and decks. Eye injuries occur when working with hatch closures, cleaning of holds, mooring operations, plumbing work. 6. Foreign bodies enter during the transportation of bulk cargo (sand, gravel), grain, work on the cleaning of holds, scrapping the hull in the absence of protective equipment. Foreign bodies of the organ of vision - the predominant injury of the seamen of the transport fleet (P<0.001). 7. Based on the obtained results, a database of occupational eye traumatism on water transport is formed to describe professional features, algorithmically predictable structure depending on the area of navigation, features of the transported cargo, climatic and geographical factors.